2001
DOI: 10.1074/jbc.m106932200
|View full text |Cite
|
Sign up to set email alerts
|

Domain Mapping of Human PEX5 Reveals Functional and Structural Similarities to Saccharomyces cerevisiae Pex18p and Pex21p

Abstract: PEX5 functions as an import receptor for proteins with the type-1 peroxisomal targeting signal (PTS1). Although PEX5 is not involved in the import of PTS2-targeted proteins in yeast, it is essential for PTS2 protein import in mammalian cells. Human cells generate two isoforms of PEX5 through alternative splicing, PEX5S and PEX5L, and PEX5L contains an additional insert 37 amino acids long. Only one isoform, PEX5L, is involved in PTS2 protein import, and PEX5L physically interacts with PEX7, the import receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
131
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 90 publications
5
131
0
Order By: Relevance
“…The alternative would be to consider that binding of a PTS1 cargo protein to Pex5p also induces conformational alterations in regions of the Pex5p protein located more than 100 amino acid residues away as is the case for the Pex13p-binding domain of Pex5p (43). This possibility, however, is not supported by the observation that Pex5p-truncated versions lacking the TPR domains are still good substrates for the peroxisomal docking/translocation machinery and even for the ATPase catalyzing the export of Pex5p back into the cytosol (30,47,48). Thus, as suggested recently, it is possible that the peroxisomal targeting domain of Pex5p is a target of negative regulation exerted by the TPR domains (30).…”
Section: Discussionmentioning
confidence: 48%
“…The alternative would be to consider that binding of a PTS1 cargo protein to Pex5p also induces conformational alterations in regions of the Pex5p protein located more than 100 amino acid residues away as is the case for the Pex13p-binding domain of Pex5p (43). This possibility, however, is not supported by the observation that Pex5p-truncated versions lacking the TPR domains are still good substrates for the peroxisomal docking/translocation machinery and even for the ATPase catalyzing the export of Pex5p back into the cytosol (30,47,48). Thus, as suggested recently, it is possible that the peroxisomal targeting domain of Pex5p is a target of negative regulation exerted by the TPR domains (30).…”
Section: Discussionmentioning
confidence: 48%
“…Presently, our knowledge on the structure/function of amino acid residues 118 -639 of mammalian Pex5p is quite vast. Indeed, a variety of biochemical and structural studies have shown that this region of the protein contains the binding site for PTS1-containing cargo proteins (7,(22)(23)(24)(25)(26)(27), seven Pex14p-binding domains (43)(44)(45), and binding sites for Pex7p (11)(12)(13)(14), Pex12p (46), and Pex13p (45). In sharp contrast, not much is known regarding the role of the first 117 amino acid residues of Pex5p.…”
Section: Pex5p Lacking the First 110 Amino Acid Residues Is Efficientmentioning
confidence: 99%
“…This peroxin recognizes a degenerated nona-peptide complying to the consensus sequence (R/K)(L/I/V)X 5 (H/Q)(L/A/F), the socalled peroxisomal targeting signal type 2 (PTS2) (8 -10). In mammals and plants, but not in lower eukaryotes, targeting of these PTS2-containing proteins seems to require Pex5p, suggesting that the two import pathways actually converge at the level of the PTS1 receptor (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…These two sets of genes appear to have coevolved. Mammals dispensed with the PEX20 gene by incorporating its PTS2-pathway function into an alternative exon in the PEX5 gene (Dodt et al, 2001). As a consequence, organisms such as plants and mammals that use the long (Pex5L) isoform of Pex5 to perform Pex20p-like functions, also lack a PEX8 gene.…”
Section: Evolution Of the Dependence Of Peroxisomal Matrix Protein Immentioning
confidence: 99%